Β-cyclodextrin as a Partial Replacement of Phosphorus Flame Retardant for Poly(Lactic Acid)/Poly(Methyl Methacrylate): A More Environmental Friendly Flame-Retarded Blends. Issue 15 (13th October 2017) - Teoh, Ee Lian; Chow, Wen Shyang; Jaafar, Mariatti
ABSTRACT: β-Cyclodextrin was used together with isopropylated triaryl phosphate ester flame retardant to improve the flame resistance of poly(lactic acid)/poly(methyl methacrylate). Poly(lactic acid)/poly(methyl methacrylate)/flame-retardant blend (with and without β-cyclodextrin) was evaluated using limiting oxygen index, Underwriters Laboratories-94 vertical burning test, scanning electron microscopy, and thermogravimetric analysis (in O2 and N2 ). The addition of β-cyclodextrin was able to reduce the amount of flame retardant required for poly(lactic acid)/poly(methyl methacrylate) blends to achieve self-extinguishing properties. The poly(lactic acid)/poly(methyl methacrylate)20/flame-retardant/β-cyclodextrin blends achieved Underwriters Laboratories-94, V-0, and limiting oxygen index value of 29.3%. A compact and wide coverage of char layer was formed on the burning surface of poly(lactic acid)/poly(methyl methacrylate)20/flame-retardant/β-cyclodextrin blends. GRAPHICAL ABSTRACT: